Outdoor Micro-Climate Analysis of Green Buildings on Environmental Affects Using PALM Software - Shahidan, Shahiron; Martha, H. Garudea; Moriwaki, Ryo; Awaludin, Ali; Supraba, Intan; Utami, Sesotya (International Journal of Integrated Engineering, 2021)
This paper aims to analyse the effect of green buildings towards the environment, which is currently affected by climate change and other problems. Two kinds of comparisons are analysed in this study; 1) A comparison between an area with conventional buildings and an area with green rooftops and 2) A comparison between green rooftops and green floors. Both conventional buildings and green rooftops have as much as 25% of green areas out of a total area measuring 200m2 x 200m2. The results showed that the best microclimate area is case 2 with an average potential temperature of 300.64 K. It has the best performance for potential temperature because of the balanced condition between H/W ratio (0.3) and solar radiation in the area. Case 1 has full width that produces good air circulation, but excessive distance between buildings also allows more solar radiation in the area. Moreover, every material has the ability to retain solar radiation (U-value) which affects the value of potential temperature. On the other hand, case 3 has a closer distance between buildings which results in zero air circulation between buildings and a higher temperature